Metal-free activated carbon fiber-based catalyst as well as preparation method and application thereof
Through the synergistic effect of carbohydrate polydopamine modified activated carbon fiber (PDAC/ACF) and persulfate (PMS), the problem of low SMX removal efficiency in the prior art is solved, and an efficient, economical and environmentally friendly SMX degradation effect is achieved.
Patent Information
- Application Number
- CN202411767965.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The prior art is not efficient, expensive or complicated to remove antibiotic sulfamethoxazole (SMX) in wastewater, and traditional activated carbon adsorption has problems such as fast saturation speed and difficulty in regeneration.
The efficient removal of SMX is achieved by carbide polydopamine modified activated carbon fibers (PDAC/ACF) combined with activated persulfate (PMS). This material activates PMS at room temperature through nitrogen doping characteristics, promoting rapid degradation of SMX.
The removal efficiency of SMX is achieved by more than 90% which is much higher than the performance of traditional ACFs, and due to the absence of metal catalysts, secondary pollution is avoided, and it is environmentally friendly and sustainable.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental engineering water treatment, and relates to a metal-free activated carbon fiber-based catalyst and a preparation method and application thereof, in particular to a new catalytic material technology for efficiently removing the antibiotic sulfamethoxazole (SMX) in wastewater, which realizes the activation of persulfate (PMS) and the efficient degradation of pollutants by carbonizing polydopamine modified activated carbon fiber (PDAC / ACF). Background Art
[0002] Sulfamethoxazole (SMX) is a widely used antibiotic that has attracted the attention of environmental scientists due to its high stability and biological activity in natural water bodies. Studies have shown that the residue of SMX in the environment may lead to the increase of bacterial resistance. For example, a study pointed out that the concentration of SMX detected at the outlet of urban wastewater treatment plants is often as high as hundreds of nanograms per liter, which is enough to affect the structure of microbial communities in aquatic ecosystems. In addition, the potential risks of SMX to human health cannot be ignored. Long-term exposure to trace amounts of SMX may cause allergic reactions or even more serious health problems. Although a variety of technologies have been developed for the removal of SMX from water, including biodegradation, adsorption, and advanced oxidation processes, these methods often have disadvantages such as low efficiency, high cost, or complex operation. For example, although traditional activated carbon adsorption can remove SMX from water, its saturation rate is fast and regeneration is difficult, with low economic benefits. In addition, although advanced oxidation processes can effectively degrade SMX, they have high operating costs and may produce toxic byproducts. In view of the shortcomings of the prior art, the present invention proposes a new type of carbonized polydopamine modified activated carbon fiber (ACF), which combines the dual functions of adsorption and catalytic activation of persulfate (PMS), aiming to achieve efficient removal of SMX in an economical and efficient manner. The introduction of carbonized polydopamine (PDA) not only enhances the structural stability of ACF, but also enhances the catalytic activity through its inherent nitrogen doping characteristics, so that it can effectively activate PMS at room temperature, thereby promoting the rapid degradation of SMX. Experiments show that the removal efficiency of SMX by this material can reach more than 90%, which is much higher than the performance of traditional ACF. Another significant advantage of the present invention is environmental friendliness and sustainability. Since PDAC / ACF can activate PMS without adding external metal catalysts, heavy metal ions that may cause secondary pollution are not introduced.
[0003] In the technical research on the degradation of sulfamethoxazole (SMX) by activating PMS with polydopamine materials, some researchers first prepared carbonized polydopamine (PDAC), and then used β-cyclodextrin to functionalize it to obtain β-CD@PDAC catalyst. The host-guest specific selective adsorption of β-cyclodextrin can assist nitrogen-doped carbon-based catalysts to selectively oxidize target pollutants and improve the removal effect of SMX; Jiang Y et al. used Fe(NO3)3·9H2O, dopamine hydrochloride and melamine as precursors to prepare nitrogen-doped carbon materials. Under the optimal experimental conditions, they had a good degradation effect on SMX. Within 30 minutes, more than 99.00% of SMX was degraded. Cao X et al. used expired drugs as endogenous nitrogen sources and DCDA as exogenous nitrogen sources to prepare carbon-based PMS activators with high nitrogen doping levels. It can achieve efficient degradation of SMX in a very short time, and achieve ultra-fast degradation of SMX within 2 minutes. Summary of the invention
[0004] The purpose of the present invention is to provide a metal-free activated carbon fiber-based catalyst in order to improve the deficiencies of the prior art. Another purpose of the present invention is to provide a method for preparing the above catalyst. Another purpose of the present invention is to provide the use of the above catalyst in degrading SMX in wastewater. The catalyst is a carbonized polydopamine-modified activated carbon fiber catalyst (PDAC / ACF), which significantly improves the degradation efficiency of SMX by utilizing the synergistic effect between ACF and polydopamine in a metal-free catalyst manner.
[0005] The technical solution of the present invention is: a metal-free activated carbon fiber-based catalyst, characterized in that the metal-free activated carbon fiber-based catalyst is an activated carbon fiber catalyst modified with carbonized polydopamine, wherein the mass ratio of carbonized polydopamine PDAC to activated carbon fiber ACF is 1:(10~20).
[0006] The present invention also provides a method for preparing the above-mentioned metal-free activated carbon fiber-based catalyst, and the specific steps are as follows:
[0007] (1) Pretreatment of activated carbon fiber: First, an acid solution is added to the (original) activated carbon fiber, and then the suspension is stirred evenly and fully contacted for acid treatment; then filtered, and the activated carbon fiber sample is repeatedly washed with distilled water until the pH value of the filtrate is neutral (6.5-7.5); then the sample is vacuum dried; the resulting sample is named ACF;
[0008] (2) Loading polydopamine: prepare a solution containing ethanol and deionized water in a container, add ammonia water and the ACF pretreated in step (1) to the above mixed solution, and stir at room temperature for a certain period of time; then add dopamine precursor under magnetic stirring conditions, and maintain the magnetic stirring conditions for a period of time to allow dopamine to self-polymerize; then slowly add acetone dropwise while stirring rapidly, and let it stand after the addition is completed; after standing, collect the precipitate, dry it under vacuum conditions, and freeze-dry it after the acetone evaporates to obtain ACF loaded with polydopamine (PDA / ACF);
[0009] (3) Forming a polymer coating on ACF: The ACF loaded with dopamine is subjected to high temperature treatment under an inert atmosphere to carbonize the dopamine. After the reaction is completed, the obtained sample is repeatedly washed and vacuum dried to obtain a metal-free activated carbon fiber-based catalyst PDAC / ACF.
[0010] Preferably, the acid solution in step (1) is at least one of hydrochloric acid or sulfuric acid; the mass concentration of the acid solution is 5-10%; the volume ratio of the mass of the activated carbon fiber to the acid solution is 20-40 g·L -1 The stirring speed is 200-400 rpm, and the stirring time is 2-4 hours; the pH value of the filtrate is washed to 6.5-7.5; the vacuum drying temperature is 60-90° C., and the vacuum drying time is 12-14 hours.
[0011] Preferably, the volume fraction of ethanol in step (2) is 20-30%; the volume ratio of the dropwise added ammonia water to the ethanol aqueous solution is (3-6):100; the volume ratio of the added ACF mass to the ethanol solution is 10-30 g·L -1 ; The stirring time at room temperature is 30 to 60 minutes, and the rotation speed is 250 to 300 rpm; the dopamine precursor is dopamine hydrochloride; the mass ratio of dopamine hydrochloride to ACF is 1:(1 to 3), and the stirring time is 18 to 30 hours; the volume ratio of the added acetone to the ethanol aqueous solution is 1.5 to 2.5:1; the static sedimentation time is 18 to 30 hours; the vacuum drying temperature is 50 to 60°C, and the time is 20 to 40 minutes; the freeze-drying time is 10 to 14 hours, and the temperature is -50 to -60°C.
[0012] Preferably, the temperature of the high temperature treatment in step (3) is 750-850°C, and the holding time is 1-3 hours; the vacuum drying temperature is 50-60°C, and the time is 12-14 hours.
[0013] Preferably, the deionized water washing in steps (1) and (3) is performed until the pH value of the filtrate is 6.5 to 7.5.
[0014] The present invention also provides the use of the above-mentioned metal-free activated carbon fiber-based catalyst in the degradation of sulfamethoxazole SMX in wastewater. The specific steps are: adding the metal-free activated carbon fiber-based catalyst and PMS to the simulated SMX wastewater, placing it in a constant temperature shaking bed for shaking reaction; wherein the pH of the simulated wastewater is adjusted to 2.00-12.00, and the SMX concentration is 10-40 mg·L -1 , the PMS dosing concentration is 1.00~2.00mM, and the adsorbent dosing mass and wastewater solution are 0.5~2g·L -1 The rotation speed in the shaking bed was set to 150-170 rpm, and the shaking reaction was carried out at 25-55°C for 1-3 hours.
[0015] Beneficial effects:
[0016] (1) Synergistic effect of adsorption and activation of PMS: By modifying the carbonized polydopamine coating on the activated carbon fiber, the present invention not only provides excellent adsorption performance, but also significantly enhances the activation ability of PMS. This synergistic effect significantly improves the degradation efficiency of SMX, especially in complex water environments.
[0017] (2) No metal catalyst, avoiding secondary pollution: Using metal-free carbonized polydopamine as an activator avoids the environmental pollution problems that may be caused by traditional metal catalysts. In addition, the catalyst can be recycled multiple times through a simple regeneration process after the reaction, further reducing processing costs and reducing resource consumption.
[0018] (3) Improving the degradation efficiency of SMX: By utilizing the synergistic effect between the carrier ACF and polydopamine, the present invention overcomes the problem of limited ability of a single activated carbon fiber-based material to activate PMS and low catalytic efficiency, and achieves efficient degradation of SMX.
[0019] (4) Selective oxidation via non-radical pathways: This catalytic system can selectively oxidize and degrade SMX in complex water environments via a non-radical mechanism, which provides the possibility for targeted treatment of specific pollutants and helps improve the accuracy and efficiency of treatment.
[0020] (5) Promote the development of practical applications: The present invention provides a new way for activated carbon fiber-based materials to activate PMS to selectively degrade typical antibiotics in wastewater in practical applications. This unique technology is not only innovative in academics, but also shows great potential and wide applicability in industrial applications due to its economic efficiency. DETAILED DESCRIPTION
[0021] In order to better understand the present invention, the present invention is further described below by way of examples, which are only used for explanation and do not constitute any limitation to the present invention.
[0022] Embodiment 1:
[0023] (1) Prepare simulated wastewater containing SMX, with an SMX concentration of 10 mg·L -1 , the pH was adjusted to 2 using 0.1 M NaOH and HCl.
[0024] (2) Preparation of catalyst, the steps are as follows:
[0025] (a) Acid-treated ACF: 10 g of untreated activated carbon fiber was cut into small cubes of 1 cm by 1 cm. The activated carbon fiber was pretreated with 500 ml of 5% HCl solution, and then the suspension was stirred at 200 rpm for 4 hours at room temperature before further treatment. After filtration, the activated carbon fiber sample was washed with deionized water until the pH value of the filtrate was 6.5. The sample was then vacuum dried at 60 ° C for 14 h, and the resulting sample was named ACF.
[0026] (b) Preparation of PDA / ACF: a. Prepare 100 ml of 20% ethanol aqueous solution and transfer it into a container; b. Add 3.0 ml of ammonia water to the above ethanol aqueous solution, and add 1.0 g of ACF in step (1), then stir magnetically for 30 min at room temperature at a speed of 300 rpm; c. Add 1.0 g of dopamine hydrochloride under stirring conditions, and continue stirring for 18 h; d. While maintaining stirring conditions, slowly drop 150 ml of acetone into the container, and let it stand for 18 h after the addition is completed; e. Filter to remove the supernatant and collect the precipitate, and vacuum dry the precipitate for 40 min at a temperature of 50°C; f. After vacuum drying, transfer to freeze drying for 10 h at a temperature of -60°C to obtain a sample PDA / ACF.
[0027] (c) Formation of polymer coating on ACF: PDA / ACF was calcined at 750°C in a tube furnace under N2 atmosphere for 3 h; after cooling to room temperature, the sample was washed with deionized water several times until the pH of the filtrate was 6.5, and then transferred to vacuum drying for 14 h at 50°C. The obtained sample was recorded as PDAC / ACF. The mass ratio of carbonized polydopamine (PDAC) to activated carbon fiber (ACF) was 1:10.
[0028] (3) Weigh 0.05 g of the catalyst PDAC / ACF prepared in this example, measure 100 ml of the simulated wastewater containing SMX prepared in step (1), put PDAC / ACF into the simulated wastewater, add 1.0 mM PMS, and react at 25°C for 180 min at a constant temperature of 150 rpm. Use high performance liquid chromatography to detect the SMX concentration. When the pH is 2, the SMX removal rate is 91.19%. The catalyst is recovered and reused. Under the same conditions, it is reused 5 times, and the removal rate is 88.69%.
[0029] Embodiment 2:
[0030] (1) Prepare simulated wastewater containing SMX, with an SMX concentration of 20 mg·L -1 , the pH was adjusted to 7 using 0.1 M NaOH and HCl.
[0031] (2) Preparation of catalyst, the steps are as follows:
[0032] (a) Acid-treated ACF: 15 g of untreated activated carbon fiber was cut into small cubes of 1 cm by 1 cm. The activated carbon fiber was pretreated with 500 ml of 10% HCl solution, and then the suspension was stirred at 300 rpm for 3 hours at room temperature before further treatment. After filtration, the activated carbon fiber sample was washed with deionized water until the pH value of the filtrate was 7.0. The sample was then vacuum dried at 80 ° C for 13 h, and the resulting sample was named ACF.
[0033] (b) Preparation of PDA / ACF: a. Prepare 100 ml of 30% ethanol aqueous solution and transfer it into a container; b. Add 5.0 ml of ammonia water to the above ethanol aqueous solution, and add 2.0 g of ACF in step (1), then stir magnetically at room temperature for 45 min at a speed of 275 rpm; c. Add 1.0 g of dopamine hydrochloride under stirring conditions, and continue stirring for 24 h; d. While maintaining stirring conditions, slowly drop 200 ml of acetone into the container, and after the addition is completed, let it stand for 24 h; e. Filter and remove the supernatant to collect the precipitate, and vacuum dry the precipitate for 30 min at a temperature of 55°C; f. After vacuum drying, transfer to freeze drying for 12 h at a temperature of -55°C to obtain a sample PDA / ACF.
[0034] (c) Formation of polymer coating on ACF: PDA / ACF was calcined at 800°C in a tube furnace under N2 atmosphere for 2 h; after cooling to room temperature, the sample was washed with deionized water several times until the pH of the filtrate was 7, and then transferred to vacuum drying for 12 h at 55°C. The obtained sample was recorded as PDAC / ACF. The mass ratio of carbonized polydopamine (PDAC) to activated carbon fiber (ACF) was 1:15.
[0035] (3) Weigh 0.1 g of the catalyst PDAC / ACF prepared in this example, measure 100 ml of the simulated wastewater containing SMX prepared in step (1), put PDAC / ACF into the simulated wastewater, add 1.0 mM PMS, and react at 35°C for 120 min at a constant temperature of 160 rpm. Use high performance liquid chromatography to detect the SMX concentration. When the pH is 7, the SMX removal rate is 95.47%. The catalyst is recovered and reused. It was reused 5 times under the same conditions, and the removal rate was 91.42%.
[0036] Embodiment 3:
[0037] (1) Prepare simulated wastewater containing SMX, with an SMX concentration of 40 mg·L -1 , the pH was adjusted to 12 using 0.1 M NaOH and HCl.
[0038] (2) Preparation of catalyst, the steps are as follows:
[0039] (a) Acid-treated ACF: 20 g of untreated activated carbon fiber was cut into small cubes of 1*1 cm, and the activated carbon fiber was pretreated with 500 ml of 5% H2SO4 solution, and then the suspension was stirred at 400 rpm for 2 hours at room temperature before further treatment. After filtration, the activated carbon fiber sample was washed with deionized water until the pH value of the filtrate was 7.5. The sample was then vacuum dried at 90 ° C for 12 h, and the resulting sample was named ACF.
[0040] (b) Preparation of PDA / ACF: a. Prepare 100 ml of 20% ethanol aqueous solution and transfer it into a container; b. Add 6.0 ml of ammonia water to the above ethanol aqueous solution, and add 3.0 g of ACF in step (1), and then stir magnetically at room temperature for 60 min at a speed of 250 rpm; c. Add 1.0 g of dopamine hydrochloride under stirring conditions and continue stirring for 30 h; d. While maintaining stirring conditions, slowly drop 250 ml of acetone into the container, and let it stand for 30 h after the addition is completed; e. Filter to remove the supernatant and collect the precipitate, and vacuum dry the precipitate for 20 min at a temperature of 60°C; f. After vacuum drying, transfer to freeze drying for 14 h at a temperature of -50°C to obtain a sample PDA / ACF.
[0041] (c) Formation of polymer coating on ACF: PDA / ACF was calcined at 850°C in a tube furnace under N2 atmosphere for 1 h; after cooling to room temperature, the sample was washed with deionized water several times until the pH of the filtrate was 7.5, and then transferred to vacuum drying for 12 h at 60°C. The obtained sample was recorded as PDAC / ACF. The mass ratio of carbonized polydopamine (PDAC) to activated carbon fiber (ACF) was 1:20.
[0042] (3) Weigh 0.2 g of the catalyst PDAC / ACF prepared in this example, measure 100 ml of the simulated wastewater containing SMX prepared in step (1), put PDAC / ACF into the simulated wastewater, add 2.0 mM PMS, and react at 45°C for 60 min at a constant temperature of 170 rpm. Use high performance liquid chromatography to detect the SMX concentration. When the pH is 12, the SMX removal rate is 93.22%. The catalyst is recovered and reused. It is reused 5 times under the same conditions, and the removal rate is 89.46%.
Claims
1. A metal-free activated carbon fiber-based catalyst, characterized in that The metal-free activated carbon fiber-based catalyst is an activated carbon fiber catalyst modified by carbonized polydopamine, wherein the mass ratio of carbonized polydopamine PDAC to activated carbon fiber ACF is 1:(10-20).
2. A method for preparing the metal-free activated carbon fiber-based catalyst as claimed in claim 1, wherein the specific steps are as follows: (1) Pretreatment of activated carbon fiber: first, an acid solution is added to the activated carbon fiber, and then the suspension is stirred evenly and fully contacted for acid treatment; then filtered, and the activated carbon fiber sample is repeatedly washed with distilled water until the pH value of the filtrate is neutral; then the sample is vacuum dried; the obtained sample is named ACF; (2) Loading polydopamine: preparing a solution containing ethanol and deionized water in a container, adding ammonia water and the ACF pretreated in step (1) to the mixed solution, stirring for a certain period of time; then adding dopamine precursor under magnetic stirring conditions, and maintaining the magnetic stirring conditions for a period of time to allow dopamine to self-polymerize; Then add acetone dropwise and let it stand after the addition is complete; After standing, the precipitate was collected and dried under vacuum conditions, and after the acetone evaporated, it was freeze-dried to obtain the ACF loaded with polydopamine; (3) Forming a polymer coating on ACF: The ACF loaded with dopamine is subjected to high temperature treatment under an inert atmosphere to carbonize the dopamine. After the reaction is completed, the obtained sample is repeatedly washed and vacuum dried to obtain a metal-free activated carbon fiber-based catalyst PDAC / ACF.
3. The method according to claim 2, characterized in that The acid solution in step (1) is at least one of hydrochloric acid or sulfuric acid; the mass concentration of the acid solution is 5-10%; the volume ratio of the mass of the activated carbon fiber to the acid solution is 20-40 g·L -1 The stirring speed is 200-400 rpm, and the stirring time is 2-4 hours; the pH value of the filtrate is washed to 6.5-7.5; the vacuum drying temperature is 60-90° C., and the vacuum drying time is 12-14 hours.
4. The method according to claim 2, characterized in that The volume fraction of ethanol in step (2) is 20-30%; the volume ratio of the added ammonia water to the ethanol aqueous solution is (3-6):100; the volume ratio of the added ACF mass to the ethanol solution is 10-30 g·L -1 ; The stirring time is 30 to 60 minutes, and the rotation speed is 250 to 300 rpm; the dopamine precursor is dopamine hydrochloride; the mass ratio of dopamine hydrochloride to ACF is 1:(1 to 3), and the stirring time is 18 to 30 hours; the volume ratio of the added acetone to the ethanol aqueous solution is 1.5 to 2.5:1; the static sedimentation time is 18 to 30 hours; the vacuum drying temperature is 50 to 60°C, and the time is 20 to 40 minutes; the freeze-drying time is 10 to 14 hours, and the temperature is -50 to -60°C.
5. The method according to claim 2, characterized in that The temperature of the high temperature treatment in step (3) is 750-850° C., and the holding time is 1-3 hours; the vacuum drying temperature is 50-60° C., and the time is 12-14 hours.
6. The method according to claim 2, characterized in that The deionized water washing in steps (1) and (3) is performed until the pH value of the filtrate is 6.5 to 7.
5.
7. Use of the metal-free activated carbon fiber-based catalyst as claimed in claim 1 in degrading sulfamethoxazole (SMX) in wastewater.
8. The use according to claim 7, characterized in that The specific steps are as follows: adding metal-free activated carbon fiber-based catalyst and PMS to simulated SMX wastewater, and placing it in a constant temperature shaking bed for shaking reaction; wherein the pH of the simulated wastewater is adjusted to 2.00-12.00, and the SMX concentration is 10-40 mg·L -1 , the PMS dosing concentration is 1.00~2.00mM, and the adsorbent dosing mass and wastewater solution are 0.5~2g·L -1 The rotation speed in the shaking bed was set to 150-170 rpm, and the shaking reaction was carried out at 25-55°C for 1-3 hours.
Citation Information
Patent Citations
Functionalized polydopamine derived carbon layer coated carbon substrate preparation method and application
CN106340399A
Blocky indium sulfide-carbon fiber network photocatalyst as well as preparation method and application thereof
CN112275297A
Catalyst for selectively oxidizing sulfamethoxazole by activating peroxymonosulfate as well as preparation and application of catalyst
CN115430448A
Preparation method of oriented self-supporting carbon nanofiber composite membrane electrode
CN116332291A
Activated carbon fiber felt and preparation method thereof
CN117920135A